2016
DOI: 10.3390/ijms17030316
|View full text |Cite
|
Sign up to set email alerts
|

Laminin Receptor-Avid Nanotherapeutic EGCg-AuNPs as a Potential Alternative Therapeutic Approach to Prevent Restenosis

Abstract: In our efforts to develop new approaches to treat and prevent human vascular diseases, we report herein our results on the proliferation and migration of human smooth muscles cells (SMCs) and endothelial cells (ECs) using epigallocatechin-3-gallate conjugated gold nanoparticles (EGCg-AuNPs) as possible alternatives to drug coated stents. Detailed in vitro stability studies of EGCg-AuNPs in various biological fluids, affinity and selectivity towards SMCs and ECs have been investigated. The EGCg-AuNPs showed sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…31 Some studies have shown that functional AuNPs conjugated with ginkgolide A can reduce VSMC proliferation and migration in vitro and neointimal hyperplasia in a mouse model, 16 and the use of epigallocatechin-3-gallate-conjugated AuNPs is considered a potential alternative approach to prevent restenosis. 32 However, the effects of naked AuNPs on the behaviors of VSMCs have been less commonly investigated. In this study, we compared four types of AuNPs, including one set of pAuNPs and three sets of cAuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…31 Some studies have shown that functional AuNPs conjugated with ginkgolide A can reduce VSMC proliferation and migration in vitro and neointimal hyperplasia in a mouse model, 16 and the use of epigallocatechin-3-gallate-conjugated AuNPs is considered a potential alternative approach to prevent restenosis. 32 However, the effects of naked AuNPs on the behaviors of VSMCs have been less commonly investigated. In this study, we compared four types of AuNPs, including one set of pAuNPs and three sets of cAuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate solutions were prepared by dissolving 10mg of EGCG in10 mL of absolute ethanol (Solution A) and dissolving 10 mg of sodium tetrachloroaurate dehydrate in 10mL of double-distilled water (solution B). We choose EGCG due to its dual action as a reducing and also as a stabilizing agent in addition to its inherent property as an anticancer agent [23,[48][49][50]. Gold nanoparticles were prepared by drop wise addition of different volumes of solution B to different volumes of solution A in a 10 mL vial placed on a magnetic hot plate with stirring for about 15 min until a ruby red color appeared.…”
Section: Preparation Of Gold Nanoparticles (Egcg-aunps)mentioning
confidence: 99%
“…Katti et. al. have demonstrated the extraordinary electron injection capability of EGCG to transform gold into gold nanoparticles, through innovative green nanotechnology, with concomitant encapsulation of tumor-avid phytochemical on the surface [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our continued quest to develop scientific rationale for Ayurvedic medicine, we have been researching, for over two decades, on the application of green nanotechnology to develop universally acceptable Ayurvedic formulations. [19][20][21][22][23][24][25][26] Green nanotechnology allows the production and efficient encapsulation of Ayurvedic-relevant phytochemicals on gold nanoparticles. Our long-standing scientific efforts, with a focus on gold nanoparticles, are based on the rationale that in Ayurvedic medicine, gold metal is ubiquitously used in combination with phytochemicals from various herbs including cinnamon, clove, gooseberry, grape, mango, turmeric and a host of herbs.…”
Section: Introductionmentioning
confidence: 99%
“…Our long-standing scientific efforts, with a focus on gold nanoparticles, are based on the rationale that in Ayurvedic medicine, gold metal is ubiquitously used in combination with phytochemicals from various herbs including cinnamon, clove, gooseberry, grape, mango, turmeric and a host of herbs. [19][20][21][22][23][24][25][26] Our efforts, serendipitously, led to a series of discoveries confirming that the phytochemicals used in Ayurvedic medicines are indeed electron-rich antioxidants and that the interaction of gold metallic precursors with phytochemically-harnessed electrons produced herb/ phytochemicals-encapsulated, well-defined, gold nanoparticles. The large surface area of gold nanoparticles embedded with atomically active nano surface motif allowed highly efficient encapsulation of phytochemical-(s)thus paving, for the first time, an innovative green nanotechnology route providing reproducible and scientifically verifiable Nano-Ayurvedic formulations.…”
Section: Introductionmentioning
confidence: 99%